PENGARUH MOTIVASI TERHADAP PENINGKATAN SEMANGAT KERJA PEGAWAI PADA KANTOR KELURAHAN DADIMULYA KECAMATAN SAMARINDA ULU KALIMANTAN TIMUR - Lestari, Mei Tri (PREDIKSI, 2016)
Effect of Motivation Toward Improved Employee Morale At Village Office District Dadimulya Borneo Samarinda Ulu Timur.Tujuan study aims to determine this positive effect on increasing motivation seemangat employee at the Village office Dadimulya district east Borneo Samarinda Ulu and to obtain data the author uses questionnaires to all employees who serve a population that is, of the two data are variable data and variable data increased motivation of employee morale at Village Office District Dadimulya Borneo Samarinda Ulu Timur.Dari the presentation of data addressing the motivation variable and increase morale in the category of extremely powerful and tredapat Relations Positive Motivation Against Against Increasing Employee Morale At Village Office Dadimulya Samarinda Ulu district of East Kalimantan